O processo psicodiagnóstico em unidades básicas de saúde - Santos, Gilcinéia Rose Silva dos (2009)
This research aims at trying to understand how the psychologists, who work at the Basic Health Units (HBU), develop the child`s psychodyagnosis, what their intentions are when they do that, how they evaluate their patients as an attempt to know them, and also which is the role of college education when carrying out such procedure. First of all, it shows the current psychodyagnosis models, the public health policies in the country, the clinical praxis in health institutions and the professional education required for this performance. Secondly, it presents a qualitative research which used semi-directed interviews with psychologists who work at HBUs in Maringa city whose purpose is to understand how they accomplished the psychodyagnosis, and which is the role of college education received during the Psychology course for such activity performance at the HBUs. The analysis favored three aspects: education and working reality at the HBUs; resources for working at the HBUs: and the use of psychodyagnosis at the HBUs. The final analysis allowed us to show that the psychologists were prepared to use the psychodyagnosis based in classical performance models which do not consider the conditions of public health institutions. They face a high number of conflicts and contradictions in the use of psychodyagnosis at the HBUs, both in the use of the traditional model and in the attempts for adapting it to single situations, like the public health system one